The Exception of National Treatment Principle of Gatt in Indonesia - Probosambodo, Yokhebed Arumdika (Universitas Internasional Batam, 2018)
The purpose of this study is to describe clearly and carefully about the exception of National Treatment principle of the GATT/WTO whether it is justifiable or not. It also aims to analyze the obstacles that hinder Indonesia in implementing international agreements, in particular the National Treatment principle of GATT/WTO completely, and to find out the consequences if Indonesia continues to apply the exceptions of the National Treatment principle of GATT/WTO. Based on the result of this research showed that the exceptions of the National Treatment principle that was imposed by Indonesia was violating the rule of GATT/WTO. Furthermore, the uncertain regulation and the confusion are the obstacles that hinder Indonesia in implementing the National Treatment principle of GATT/WTO completely, thus Indonesia should make a clearly decision whether it is a Monism or a Dualism country to determine which law should be more supreme, International Law or National Law?. The consequences impose on a state when violating a GATT/WTO agreement is very influential and harms the state itself, because it would be excommunicated from the international trade.